2017
DOI: 10.1007/s00436-017-5562-3
|View full text |Cite
|
Sign up to set email alerts
|

Haemosporidian prevalence and parasitaemia in the Black-throated sparrow (Amphispiza bilineata) in central-Mexican dryland habitats

Abstract: To date it is not well-understood how seasonality and human-induced habitat change may affect haemosporidian prevalence and parasitaemia in bird hosts in dryland habitats. We compared haemosporidian prevalence and parasitaemia between habitat types, including Yucca-dominated scrublands (closed habitat) and creosotebush scrublands (open habitat), and between seasons, including non-breeding (dry) and breeding (wet) in the Black-throated sparrow (Amphispiza bilineata) at semi-arid scrublands of Central Mexico. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
1
14
0
3
Order By: Relevance
“…One recent study from northern South America, reported that diversity and prevalence of Plasmodium and Haemoproteus responded to host species and to host by climate interactions, but not to water availability (Pulgarín-R et al 2018). In contrast, in drier environments that are topographically less complex, recorded prevalence of Leucocytozoon is usually extremely low (e.g., Belo et al 2012;Reinoso-Pérez et al 2016;Ham-Dueñas et al 2017).…”
Section: Effect Of Watermentioning
confidence: 99%
See 2 more Smart Citations
“…One recent study from northern South America, reported that diversity and prevalence of Plasmodium and Haemoproteus responded to host species and to host by climate interactions, but not to water availability (Pulgarín-R et al 2018). In contrast, in drier environments that are topographically less complex, recorded prevalence of Leucocytozoon is usually extremely low (e.g., Belo et al 2012;Reinoso-Pérez et al 2016;Ham-Dueñas et al 2017).…”
Section: Effect Of Watermentioning
confidence: 99%
“…Therefore, in some dry landscapes such as in Arizona, absence of haemosporidians may result from very limited water availability (Deviche et al 2005). In other cases, such as in dry scrublands of central Mexico, where local inhabitants build water ponds for livestock management and where the density of these ponds is high, haemosporidian assemblages are species rich and both prevalence and parasitaemia decrease with increasing distance from such water sources, but again, the magnitude of response varies among bird and parasite species (Reinoso-Pérez et al 2016;Ham-Dueñas et al 2017). Moreover, in this region, the effect of distance from water ponds may be confounded with habitat degradation (see section 10.4.2 below).…”
Section: Effect Of Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Although higher prevalence has been tied to reproduction of the host (e.g. Knowles et al, 2011;Ham-Dueñas et al, 2017), this scenario is not plausible given the apparently continuous reproduction of Z. capensis at the study site (Cadena-Ortiz, personal observation), which contrasts with reports of reproduction seasonality in two other nearby localities, but at higher elevation (Papallacta at 3300 m a.s.l. and Pintag at 2900 m a.s.l.…”
Section: Factors Associated With Haemosporidian Infectionsmentioning
confidence: 73%
“…Haemoproteus sp. ZC1 infects Z. capensis in Peru (Jones et al ., 2013), other Emberizidae in México (Reinoso-Pérez et al ., 2016; Ham-Dueñas et al ., 2017), and Troglodytes aedon in Peru (Galen and Witt, 2014). This lineage shows considerable genetic distance from those of other Haemoproteus morphospecies (Fig.…”
Section: Discussionmentioning
confidence: 99%